MEMBANGUN DESA DENGAN KEARIFAN LOKAL DI DESA PALAAN KECAMATAN NGAJUM KABUPATEN MALANG - Handayani, Sri; Bisri, Mashur Hasan (Journal of Urban Sociology, 2020)
This study aims to discuss the use of local wisdom in village development. Local wisdom that has become a local culture and is routinely implemented all contains norms, arts, mutual cooperation and togetherness in rural communities such as; traditional ceremonies, cultural activities, religious activities, and community social activities. The principle of recommendation and subsidiarity gives the village recognition and authority to be empowered and independent. Law Number 6 of 2014 concerning Villages is a policy affirmative so that villages can carry out various forms of development in all. The implementation of development requires the harmonization of all aspects of society so that it can fulfill the stages of the development process, from planning, implementation and accountability. Evaluation of development policies can be carried out based on existing noble values. The research was conducted using qualitative methods. Data search interview techniques for primary data and accommodate existing data and documentation in the village for secondary data. The result of this research is the role of local wisdom in Palaan Village by running the village community development will have a very significant relationship. Local wisdom that is cultural in nature such as traditional ceremonies carried out in the framework of pre-implementation of activities for infrastructure development, the form of activities funded by APBDesa is art groups.Keywords: Local wisdom, village authority, village development.